Towards evaluating social telepresence in mobile context - Pang, Natalie (2013)
In this paper we analyze the state-of-art in the evaluation of telepresence, social presence and copresence and propose a qualitative approach for evaluating social telepresence in mobile context. Our approach aims to meet the need of rapidly growing industries of mixed reality, social media and video broadcasting services.